Hyperkalemia Diagnosis and Management for a Total AV Block Patient with a Pseudo-STEMI Infarction Pattern: A Case Report: Pseudo-STEMI Pattern in Hyperkalemia Patient with Total AV Block - Sofi, Sofi Aliyatul Himah; Perdana, Hidayanto (Universitas Airlangga, 2024)
Highlights: 1. A surprising finding in which manifestation of hyperkalemia depends on potassium levels and comorbidities. 2. The manifestation as ST elevation and total AV block are considered rare cases, which is why this article is very interesting to read. - Background: Hyperkalemia is an electrolytic disorder that is often encountered in hospitals and may be life-threatening. The ECG abnormalities that occur vary from tall T to deadly arrhythmia. ST segment elevation is rarely encountered and may be confused for the alternative diagnosis of myocardial infarction. Case Summary: The patient is a 53 year-old male with total AV block with an ECG pseudo-STEMI infarction pattern. Initial diagnosis was acute myocardial infarction; it was then known that the patient suffered from chronic kidney disease with hyperkalemia. The patient recovered after obtaining hyperkalemia therapy. Conclusion: In summary, hyperkalemia manifestation on ECG depends on potassium levels and comorbidities. Manifestation as ST segment elevation and total AV block are rare case, prompt diagnosis and right treatment may reduce the mortality.